2008
DOI: 10.1016/j.hal.2007.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Field and mesocosm trials on passive sampling for the study of adsorption and desorption behaviour of lipophilic toxins with a focus on OA and DTX1

Abstract: Abstract:It has been demonstrated that polymeric resins can be used as receiving phase in passive samplers designed for the detection of lipophilic marine toxins at sea and was referred to as solid phase adsorption toxin tracking (SPATT). The present study describes the uptake and desorption behaviour of the lipophilic marine toxins okadaic acid (OA) and dinophysistoxin-1 (DTX1) from Prorocentrum lima cultures by five styrene-divinylbenzene based polymeric resins Sepabeads ® SP850, Sepabeads ® SP825L, Amberlit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
74
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(81 citation statements)
references
References 21 publications
(24 reference statements)
3
74
2
Order By: Relevance
“…We have demonstrated the successful application of HP20 for detection of the hydrophilic toxins DA and PST in the field, and previous studies have demonstrated its applicability for lipophilic toxins (Fux et al 2009;Fux et al 2008;Mackenzie et al 2004;Pizarro et al 2008aPizarro et al , 2008bRundberget et al 2007Rundberget et al , 2009Takahashi et al 2007;Turrell et al 2007). HP20 demonstrates characteristics that perhaps most closely imitate those of a mussel, i.e., a relatively low rate of accumulation (19% over 7 d) and a relatively higher rate of desorption.…”
Section: ; Aoac International 2006)mentioning
confidence: 67%
See 1 more Smart Citation
“…We have demonstrated the successful application of HP20 for detection of the hydrophilic toxins DA and PST in the field, and previous studies have demonstrated its applicability for lipophilic toxins (Fux et al 2009;Fux et al 2008;Mackenzie et al 2004;Pizarro et al 2008aPizarro et al , 2008bRundberget et al 2007Rundberget et al , 2009Takahashi et al 2007;Turrell et al 2007). HP20 demonstrates characteristics that perhaps most closely imitate those of a mussel, i.e., a relatively low rate of accumulation (19% over 7 d) and a relatively higher rate of desorption.…”
Section: ; Aoac International 2006)mentioning
confidence: 67%
“…Extraction of a field SPATT sample is comparatively lower in time and labor requirements. The SPATT extraction described here includes a three-step series of column elutions that can be completed within 10-30 min, yielding extracts that are available for immediate analysis of a single toxin or of multiple toxins, as demonstrated (e.g., DA or DA plus PST), We note that others have already demonstrated the ability to use HP20 for a suite of marine toxins (Fux et al 2008(Fux et al , 2009Mackenzie et al 2004;Pizarro et al 2008aPizarro et al , 2008bRundberget et al 2007Rundberget et al , 2009Takahashi et al 2007). The resin and extract are reasonably stable when stored at -80°C, providing the ability to archive samples for further analysis at a later time.…”
Section: Discussionmentioning
confidence: 99%
“…23, 255-266 (2010) Table 2. level. These amounts of adsorbed toxin are low in comparison with the adsorption capability of polymeric resin for OA (Fux et al 2008). …”
Section: Toxin Detection In Biodeposits and In The Passive Adsorptionmentioning
confidence: 83%
“…Three SPATT bags were removed four times during the experiment (on the sixth, tenth, fifteenth and twentieth days). The efficiency of this technique, inspired by a study in New Zealand , has previously been established (Fux et al 2008). Sample collection and processing.…”
Section: Methodsmentioning
confidence: 99%
“…Flynn et al 1996, Wang et al 2002, Kim et al 2005. For dinoflagellates that produce hydrophobic toxins associated with DSP (diarrhoeic shellfish poisoning), toxins dissolved in the water are measured with the so-called 'SPATT (solid phase adsorption toxin tracking) bags' filled with a polymeric resin that adsorbs hydrophobic compounds (MacKenzie et al 2004, Fux et al 2008, 2009. During DSP-producing blooms, significant amounts of DSP toxins are dissolved in the seawater (MacKenzie et al 2004).…”
Section: Introductionmentioning
confidence: 99%